Common Fixed-Point Theorems in the Partial b-Metric Spaces and an Application to the System of Boundary Value Problems - Muhammad Nazam; Zahida Hamid; Hamed Al Sulami; Aftab Hussain (Journal of Function Spaces)
In this paper, we investigate the conditions for the existence of the common fixed points of generalized contractions in the partial b-metric spaces endowed with an arbitrary binary relation. We establish some unique common fixed-point theorems. The obtained results may generalize and improve earlier fixed-point results. We provide examples to illustrate our findings. As an application, we discuss the common solution to the system of boundary value problems.